(untitled) (The International Journal for Scientific Research, 2025)
The study primarily aimed to measure the role of agricultural extension in achieving food security according to sustainable agriculture mechanisms in Libya. This was achieved by achieving the following sub-objectives: identifying some of the personal, social, and communication variables that distinguish extension workers in the Libyan National Agricultural Extension Organization; measuring the overall score of the educational role of agricultural extension in achieving food security in Libya; measuring the correlation between the studied independent variables and the overall score of the educational role of agricultural extension; determining the percentages of contribution of the studied independent variables to explaining the overall variance in the overall score of the educational role of agricultural extension; and identifying the most important agricultural, extension, human, and material problems related to job satisfaction facing agricultural extension in achieving food security in Libya. To achieve these objectives, a questionnaire was designed, data for which were collected through personal interviews with a sample of 36 extension workers employed by the National Agricultural Extension Organization in the Tripoli region of Libya. Data were collected during the first quarter of 2025. Frequencies, percentages, simple correlation coefficients, and stepwise multiple regression analysis were used to analyze and present the data. The most important results were as follows: 1. The majority of respondents, 83.3%, reported that the educational role of agricultural extension is limited or average. 2. There is a correlation between the overall score on the educational role of agricultural extension and seven independent variables: age, educational qualifications, length of time working in the agricultural field, length of time working with the extension agency, the respondent’s knowledge sources, degree of innovation, and environmental and marketing information sources. 3. There are four variables that contribute to explaining the total variance in the educational role of agricultural extension, and the combined contribution of these variables to the predictive and explanatory power is 95%. 4. A proposed guidance action plan was developed for a training program directed at agricultural engineers working in agricultural extension in general, and marketing extension in particular. Care was taken to ensure that it is based on a situational study and the field results obtained by this research.